The Posthuman Reader in Postprint Literature: Between Page and Screen - Pressman, Jessica (FRAME, Journal of Literary Studies, 2026)
Amaranth Borsuk and Brad Bouse’s Between Page and Screen (2012) is an augmented reality book of poetry: a codex filled with QR (“Quick Response”) codes that activate a networked Internet connection to produce literature between the book’s pages and the reader’s computer screen. The work produces a mirror effect that depicts the human reader incorporated into the digital network that enables contemporary literature. This essay argues that Between Page and Screen’s depiction of its human reader offers an opportunity to explore how digital literature complicates traditional, print-based expectations of reading by focusing on how we readers become posthuman along with our postprint literature.